Topiramate versus carbamazepine monotherapy for epilepsy: an individual participant data review - Nevitt, Sarah J (Cochrane Database Syst Rev, 2016)
BACKGROUND: Epilepsy is a common neurological condition in which abnormal electrical discharges from the brain cause recurrent unprovoked seizures. It is believed that with effective drug treatment, up to 70% of individuals with active epilepsy have the potential to become seizure‐free and go into long‐term remission shortly after starting drug therapy, the majority of which may be able to achieve remission with a single antiepileptic drug (AED). The correct choice of first‐line antiepileptic therapy for individuals with newly diagnosed seizures is of great importance. It is important that the choice of AED for an individual is based on the highest‐quality evidence available regarding the potential benefits and harms of various treatments. It is also important to compare the efficacy and tolerability of AEDs appropriate to given seizure types. Topiramate and carbamazepine are commonly used AEDs. Performing a synthesis of the evidence from existing trials will increase the precision of results of outcomes relating to efficacy and tolerability, and may help inform a choice between the two drugs. OBJECTIVES: To assess the effects of topiramate monotherapy versus carbamazepine monotherapy for epilepsy in people with partial‐onset seizures (simple or complex partial and secondarily generalised) or generalised onset tonic‐clonic seizures (with or without other generalised seizure types). SEARCH METHODS: We searched the Cochrane Epilepsy Group Specialized Register (14 April 2016), the Cochrane Central Register of Controlled Trials (CENTRAL) (14 April 2016) and MEDLINE (Ovid, 1946 to 14 April 2016). We imposed no language restrictions. We also contacted pharmaceutical companies and trial investigators. SELECTION CRITERIA: Randomised controlled trials in children or adults with partial‐onset seizures or generalised‐onset tonic‐clonic seizures with or without other generalised seizure types with a comparison of monotherapy with either topiramate or carbamazepine. DATA COLLECTION AND ANALYSIS: This was an individual participant data (IPD) review. Our primary outcome was 'time to withdrawal of allocated treatment’, and our secondary outcomes were 'time to first seizure post randomisation’, 'time to 6‐month remission, 'time to 12‐month remission’ and incidence of adverse events. We used Cox proportional hazards regression models to obtain trial‐specific estimates of hazard ratios (HRs) with 95% confidence intervals (CIs), and used the generic inverse variance method to obtain the overall pooled HRs and 95% CIs. MAIN RESULTS: IPD were available for 1151 of 1239 eligible individuals from two of three eligible studies (93% of the potential data). A small proportion of individuals recruited into these trials had 'unclassified seizures;' for analysis purposes, these individuals are grouped with those with generalised onset seizures. For remission outcomes, a HR < 1 indicated an advantage for carbamazepine, and for first seizure and withdrawal outcomes, a HR < 1 indicated an advantage for topiramate. The main overall results, given as pooled HR adjusted for seizure type (95% CI) were: for time to withdrawal of allocated treatment 1.16 (0.98 to 1.38); time to first seizure 1.11 (0.96 to 1.29); and time to 6‐month remission 0.88 (0.76 to 1.01). There were no statistically significant differences between the drugs. A statistically significant advantage for carbamazepine was shown for time to 12‐month remission: 0.84 (0.71 to 1.00). The results of this review are applicable mainly to individuals with partial‐onset seizures; 85% of included individuals experienced seizures of this type at baseline. For individuals with partial‐onset seizures, a statistically significant advantage for carbamazepine was shown for time to withdrawal of allocated treatment (HR 1.20, 95% CI 1.00 to 1.45) and time to 12‐month remission (HR 0.84, 95% CI 0.71 to 1.00). No statistically significant differences were apparent between the drugs for other outcomes and for the limited number of individuals with generalised‐onset tonic‐clonic seizures with or without other generalised seizure types or unclassified seizures. The most commonly reported adverse events with both drugs were drowsiness or fatigue, ‘pins and needles’ (tingling sensation), headache, gastrointestinal disturbance and anxiety or depression The rate of adverse events was similar across the two drugs. We judged the methodological quality of the included trials generally to be good; however, there was some evidence that the open‐label design of the larger of the two trials may have influenced the withdrawal rate from the trial. Hence, we judged the evidence for the primary outcome of treatment withdrawal to be moderate for individuals with partial‐onset seizures and low for individuals with generalised‐onset seizures. For efficacy outcomes (first seizure, remission), we judged the evidence from this review to be high for individuals with partial‐onset seizures and moderate for individuals with generalised‐onset or unclassified seizures. AUTHORS' CONCLUSIONS: For individuals with partial‐onset seizures, there is evidence that carbamazepine is less likely to be withdrawn and that 12‐month remission will be achieved earlier than with topiramate. No differences were found between the drugs in terms of the outcomes measured in the review for individuals with generalised tonic‐clonic seizures with or without other seizure types or unclassified epilepsy; however, we encourage caution in the interpretation of these results due to the small numbers of participants with these seizure types. We recommend that future trials should be designed to the highest quality possible and take into consideration masking, choice of population, classification of seizure type, duration of follow‐up, choice of outcomes and analysis, and presentation of results.